ANSWER
![{(x - 4)}^{2} + {(y - 3)}^{2} = {2}^{2}](https://tex.z-dn.net/?f=%20%7B%28x%20-%204%29%7D%5E%7B2%7D%20%2B%20%20%7B%28y%20-%203%29%7D%5E%7B2%7D%20%20%3D%20%20%20%7B2%7D%5E%7B2%7D%20)
EXPLANATION
The equation of the circle with radius r and centre (a,b) is given by
![(x - a)^{2} + {(x - b)}^{2} = {r}^{2}](https://tex.z-dn.net/?f=%28x%20-%20a%29%5E%7B2%7D%20%20%2B%20%20%7B%28x%20-%20b%29%7D%5E%7B2%7D%20%20%3D%20%20%7Br%7D%5E%7B2%7D%20)
The radius is
![r = 2](https://tex.z-dn.net/?f=r%20%3D%202)
We need to determine the center of the circle from the given equation of another circle, which is,
![{x}^{2} + {y}^{2} - 8x - 6y + 24 = 0](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20%2B%20%20%7By%7D%5E%7B2%7D%20%20-%208x%20-%206y%20%2B%2024%20%3D%200)
We complete the square to obtain,
![{x}^{2} - 8x+ {y}^{2} - 6y + 24 = 0](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20-%208x%2B%20%20%7By%7D%5E%7B2%7D%20%20-%206y%20%2B%2024%20%3D%200)
![{x}^{2} - 8x+ {y}^{2} - 6y = - 24](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20-%208x%2B%20%20%7By%7D%5E%7B2%7D%20%20-%206y%20%20%3D%20%20-%2024)
![{x}^{2} - 8x+ {( - 4)}^{2} + {y}^{2} - 6y + {( - 3)}^{2} = - 24 + {( - 3)}^{2} + {( - 4)}^{2}](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20-%208x%2B%20%20%7B%28%20-%204%29%7D%5E%7B2%7D%20%2B%20%20%20%7By%7D%5E%7B2%7D%20%20-%206y%20%20%2B%20%20%7B%28%20-%203%29%7D%5E%7B2%7D%20%20%3D%20%20-%2024%20%2B%20%20%7B%28%20-%203%29%7D%5E%7B2%7D%20%2B%20%20%7B%28%20-%204%29%7D%5E%7B2%7D)
![{(x - 4)}^{2} + {(y - 3)}^{2} = - 24 + 9+ 16](https://tex.z-dn.net/?f=%20%7B%28x%20-%204%29%7D%5E%7B2%7D%20%2B%20%20%7B%28y%20-%203%29%7D%5E%7B2%7D%20%20%3D%20%20-%2024%20%2B%20%209%2B%20%2016)
![{(x - 4)}^{2} + {(y - 3)}^{2} = 1](https://tex.z-dn.net/?f=%20%7B%28x%20-%204%29%7D%5E%7B2%7D%20%2B%20%20%7B%28y%20-%203%29%7D%5E%7B2%7D%20%20%3D%20%201)
The centre of this circle is (4,3)
Hence the center of the circle whose equation we want to find is also (4,3).
With this center and radius 2, the required equation is,
![{(x - 4)}^{2} + {(y - 3)}^{2} = {2}^{2}](https://tex.z-dn.net/?f=%20%7B%28x%20-%204%29%7D%5E%7B2%7D%20%2B%20%20%7B%28y%20-%203%29%7D%5E%7B2%7D%20%20%3D%20%20%20%7B2%7D%5E%7B2%7D%20)
Therefore the correct answer is C.
Answer:
the answer is number 4......
Can you try rewording this question?
Answer:
m = 1/2
Step-by-step explanation:
We need to solve the equation:
3/4 = m + 1/4
In order to solve for m, we must isolate the variable - in other words, we need to move all the m terms to one side and all the non-m terms to the other.
So, subtract 1/4 from both sides to isolate m:
3/4 - 1/4 = m
m = 2/4 = 1/2
Thus, m = 1/2.
<em>~ an aesthetics lover</em>
Answer:
report me I have brainly plus